Base metal low oxygen evolution potential electrode for solid polymer water electrolysis
By using the heteropolyacid compound with Dawson structure as the core active component of base metal low oxygen analysis potential electrode, the problems of high cost of precious metal anode materials and low catalytic activity of base metal electrodes are solved, and efficient, stable and low-cost electricity are achieved Catalytic properties.
Patent Information
- Application Number
- CN202411407459.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-10
AI Technical Summary
In the existing solid polymer electrolytic technology, the high cost of precious metal anode materials and the problems of easy passivation and low catalytic activity of base metal electrodes limit their widespread promotion in practical applications.
The heteropolyacid compound with Dawson structure is used as the core active component of the base metal low oxygen potential electrode. It forms a high catalytic through specific preparation methods, including grinding, stirring, dialysis, nanofiltration and ultra-high frequency ultrasonic dispersion. Active and stable nanoparticle coating.
It achieves good morphology and catalytic activity during the electrocatalysis process, improves electrocatalytic efficiency and corrosion resistance, reduces production costs, and has long stability.
Smart Images

Figure CN119465234A_ABST
Abstract
Description
1. Technical Field
[0001] The invention relates to the field of electrochemical new energy technology, and in particular to a base metal low oxygen evolution potential electrode for solid polymer water electrolysis and a preparation method thereof. 2. Background Technology
[0002] Solid polymer electrolyte water electrolysis (SPEWE) has received widespread attention and developed rapidly since the 1970s. SPEWE technology was first proposed by General Electric Company in the United States and applied to the fuel cell system of the Gemini spacecraft, creating the field of solid polymer electrolyte (SPE) technology. Since then, SPE technology has been widely used in hydrogen-oxygen fuel cells, water electrolysis, organic electrochemical synthesis and other fields due to its advantages such as high efficiency, safety, simple structure and stable performance. Compared with traditional alkaline water electrolysis, SPE water electrolysis technology has the advantages of high efficiency (nearly 100%), high current density, high safety (using pure water as electrolyte to avoid corrosion), simple structure (no cooling system required) and long life (the longest chamber life is more than 30 years). However, SPE technology also faces some challenges, such as low ionic conductivity, low thermal stability and contact resistance of polymer solid electrolytes, which limit its widespread promotion in practical applications.
[0003] In solid polymer water electrolysis technology, commonly used anode materials mainly include precious metals such as rhodium (Ru) and iridium (Ir). These materials show good catalytic activity and stability in a strong acidic environment. For example, the combination of Nation membrane and precious metal catalyst is the core of SPE electrolysis technology, among which Nation membrane is widely used due to its good chemical stability, mechanical stability and high ionic conductivity. However, the high cost of precious metals limits the widespread application of SPE electrolysis technology. It is estimated that 700 kg of iridium or rhodium is theoretically required to obtain 1 gigawatt of electricity, while the market price of iridium and rhodium is expensive and in short supply. Therefore, the development of low-cost, high-performance anode materials has become a hot topic in current research. At present, research mainly focuses on reducing the use of precious metals and developing base metal electrodes through alloying and other methods to improve catalytic performance and reduce costs.
[0004] Base metal low oxygen evolution potential (OEP) electrodes have significant cost advantages over current precious metal anode materials. The cost of base metals is about 1 / 1000 of that of iridium, and they are expected to be used as on-site hydrogen production electrodes that combine solar power generation, wind power generation, etc. with PEM water electrolysis. In addition, base metal electrodes can also show good catalytic ability in corrosive environments and are expected to replace precious metal electrodes. For example, patent CN109478653A has developed an oxygen evolution (OER) electrode, whose metal layer includes nickel, cobalt, manganese and compounds formed by their combination, with a low OEP; patent CN115710727A involves a hollow framework high entropy oxide oxygen evolution catalyst and its preparation method; invention CN113802137A has developed an OER electrode with metal nanoclusters and metal carriers, wherein the metal nanoclusters include a core and an organic thiol-containing ligand, with a low OEP and high stability. However, base metal electrodes also face some problems, such as easy passivation and low catalytic activity. In order to solve these problems, researchers have alloyed easily passivated base metals with base metals with high catalytic ability through alloying and other methods, and developed base metal electrodes that can also show their original catalytic ability in corrosive environments. In addition, optimizing the catalytic layer structure, improving the electrode preparation method and improving the corrosion resistance of the diffusion layer are also the key to improving the performance of water electrolysis cells. III. Summary of the invention
[0005] The present invention is made in view of the problems existing in the prior art. For the problem of catalyst activity and stability, its composition and structure can be optimized, such as doping and alloying, constructing a core-shell structure; selecting suitable carriers, including metal oxides and carbon materials; developing new catalysts, such as non-precious metals and single-atom catalysts. In view of the high cost, reduce the amount of precious metals, optimize the preparation process to improve the dispersion, and develop cost-effective alternative materials and composite materials. In order to solve the problem of compatibility with the electrolyte, surface modification is carried out, the surface of the anode material is treated or additives are added to the electrolyte, and the electrode structure is optimized, three-dimensional electrodes are designed, and integrated electrodes are prepared. For the optimization of the electrode structure, the template method and freeze-drying method are used to regulate the pore structure, construct an intermediate layer, and optimize the preparation process to perform interface engineering to improve the electrode performance and compatibility with the electrolyte.
[0006] Heteropolyacid is an excellent ion conductive material. Since its structure was proposed by JF Keggin in 1933, it is generally called Keggin structure. It has complete tetrahedral symmetry, twelve coordinated atoms connected to oxygen atoms form a cage, and the core atom is in the middle. In recent studies, we have discovered a new type of Dawson structure, whose general formula is [Se 2 Mo 18 O 62 ] n- The central Se atom is SeO 4The tetrahedron is in the center, and the outside is four Mo connected at the same angle 3 O 12 Three metal clusters are connected corner by corner with the central tetrahedron. Each three metal cluster consists of three MoO 6 The octahedrons share edges, which can be regarded as two Keggin structure ions with one Mo removed. 3 O 12 The three metal clusters eventually form a 1:17 series of vacancy-type Dawson structures, which have been shown to have excellent charge conduction and chemical stability. In addition to the core heteropolyacid unit, transition metal elements and alkali metal elements as well as phosphate coordination structures need to be introduced as stabilizers. The molecular formula of the Dawson structure material is Na 8 K 18 [Sc 12 (H 2 O) 6 (OH) 3 (HPO 4 ) 2 (Se 2 Mo 18 O 62 ) 3 ]·xH 2 O. The material represented by this molecular formula is the core active component of the base metal low oxygen evolution potential electrode for solid polymer water electrolysis.
[0007] In order to achieve the above object, the technical solution of the present invention is a base metal low oxygen evolution potential electrode for solid polymer water electrolysis and a preparation method thereof, characterized in that the preparation method of the electrode comprises the following steps:
[0008] Step 1: SeCl 4 With (NH 4 ) 2 MoO 4 After being fully ground with a mortar, the mixture was added to ultrapure water and stirred vigorously to form a light yellow aqueous solution having a mixed mass concentration of 10%;
[0009] Step 2: adjust the pH value of the pale yellow aqueous solution obtained in step 1 to 4 with phosphoric acid, add excess ScCl 3 until it is completely dissolved, at which point the molar ratio of Sc to Se should be greater than 2, to obtain solution A;
[0010] Step 3, preparing a mixed solution of NaOH and KOH with a molar ratio of 4:9 and a mixed mass concentration of 25% to obtain a mixed alkaline solution B;
[0011] Step 4, adding the mixed alkali solution B obtained in step 3 dropwise into solution A, and monitoring the change of pH value, when the pH value reaches 6, the solution gradually becomes turbid, at which time the dropping is stopped and the solution is stirred vigorously, a large amount of flocs are quickly formed in solution A, but are broken again with stirring;
[0012] Step 5, after continuous stirring for 30 minutes, the stirring was stopped, and the mixture was dialyzed overnight using a 10,000Da dialysis bag. The dialysate was subjected to ultra-high-speed centrifugation at 1,5000 rpm and then separated by nanofiltration. The light yellow nanoparticles were repeatedly washed with ultrapure water and acetone, and then placed in the air to dry overnight;
[0013] Step 6, placing the solid particles obtained in step 5 into a quartz boat, calcining in a vacuum oven at 350° C. for 1 hour, and immersing the obtained black sample in an imidazole solution;
[0014] Step 7, pouring the solid particles soaked in imidazole obtained in step 6 into a ball mill, grinding for 3 hours, dialyzing again with a 10,000Da dialysis bag overnight, subjecting the obtained dialysate to ultra-high-speed centrifugation at 1,5000 rpm, and then separating by nanofiltration to obtain nanoparticles;
[0015] Step 8, dispersing the nanoparticles obtained in step 7 in a Nafion solution with a mass concentration of 5%, at which point the mass concentration of the nanoparticles is 20%, and dispersing the solution under 1 kW ultrahigh frequency ultrasound for 5 minutes to form a uniformly dispersed nanoparticle solution;
[0016] Step 9, uniformly coating the nanoparticle solution obtained in step 8 on the surface of the hydrophilic carbon paper, and drying at 150° C. for 15 minutes to obtain a carbon paper catalyst material having an oxygen evolution catalytic active coating.
[0017] The above technical solution is further limited to the following: the purity of NaOH and KOH in step 3 should be higher than 95%, and the mixture should be sealed immediately after preparation to prevent the absorption of CO in the air. 2 , the generation of bicarbonate affects the purity of the product.
[0018] For the above technical solution, it is further defined that the molecular formula of the particles obtained in step 5 is Na 8 K 18 [Sc 12 (H 2 O) 6 (OH) 3 (HPO 4 ) 2 (Se 2 Mo 18 O 62 ) 3 ]·xH 2O is a heteropolyacid compound with a vacancy-type Dawson structure.
[0019] The above technical solution is further limited to that the hydrophilic carbon paper selected in step 9 can be TGP-H-60 series carbon paper of Toray Industries, Japan, SGL-30 series carbon paper of the United States, or HCP010N series carbon paper of Sanshou Company, Shanghai, China.
[0020] The present invention is beneficial in that:
[0021] 1) The structure is highly symmetrical and stable, and can maintain a good morphology during the electrocatalytic process, providing a stable framework for the catalytic reaction.
[0022] 2) The Sc-Mo-Se elements can produce a synergistic effect to improve the catalytic activity. For example, the transition metal can adjust the electronic structure and promote the oxygen evolution reaction. It has abundant redox active sites, can effectively adsorb reaction intermediates, and reduce the reaction energy barrier.
[0023] 3) At the same time, the Dawson structure usually has good conductivity, which can accelerate electron transfer and improve electrocatalytic efficiency. In addition, the structure has a certain corrosion resistance and can maintain stability for a long time under harsh electrocatalytic conditions.
[0024] 4) Compared with other anode materials, the Dawson structure is relatively easy to synthesize and can be regulated by a variety of methods to meet different application requirements. IV. Description of the drawings
[0025] In order to more clearly illustrate the specific embodiments of the present invention, the drawings used in the description of the specific embodiments are briefly described below. Figure 1 The Dawson structure Na 8 K 18 [Sc 12 (H 2 O) 6 (OH) 3 (HPO 4 ) 2 (Se 2 Mo 18 O 62 ) 3 ]·xH 2 Transmission electron microscope image of O material;
[0026] Figure 2 For electrocatalysis using Dawson structure Na 8 K 18 [Sc 12 (H 2 O) 6 (OH)3 (HPO 4 ) 2 (Se 2 Mo 18 O 62 ) 3 ]·xH 2 X-ray diffraction image of O material.
[0027] Figure 3 The Dawson structure Na 8 K 18 [Sc 12 (H 2 O) 6 (OH) 3 (HPO 4 ) 2 (Se 2 Mo 18 O 62 ) 3 ]·xH 2 Linear sweep voltammetry curves of RuO materials compared with carbon paper and RuO 2 comparison. V. Specific implementation methods
[0028] The present invention is described in detail below with reference to the accompanying drawings and embodiments:
[0029] Embodiment 1:
[0030] A base metal low oxygen evolution potential electrode for solid polymer water electrolysis and a preparation method thereof, the preparation method of the electrode comprising the following steps: firstly, SeCl 4 With (NH 4 ) 2 MoO 4 After being fully ground with a mortar, the mixture was added into ultrapure water and stirred vigorously to form a pale yellow aqueous solution with a mixed mass concentration of 10%. The pH value of the obtained pale yellow aqueous solution was adjusted to 4 with phosphoric acid, and an excess of ScCl was added. 3 The solution was completely dissolved. At this time, the molar ratio of Sc to Se should be greater than 2, and solution A was obtained. A mixed solution of NaOH and KOH with a molar ratio of 4:9 was prepared. The mixed mass concentration was 25%. At this time, the purity of NaOH and KOH should be higher than 95%. After the preparation, it was sealed immediately to prevent CO in the air. 2Absorption, avoiding the influence of bicarbonate on the purity of the product, and obtaining a mixed alkaline solution B after mixing; adding the mixed alkaline solution B dropwise into solution A, and monitoring the change of pH value, when the pH value reaches 6, the solution gradually becomes turbid, at this time, stopping the dropping and stirring vigorously, a large number of flocs are quickly formed in solution A, but they are broken again with stirring; after continuous stirring for 30 minutes, stopping the stirring, dialyzing overnight with a 10,000Da dialysis bag, and subjecting the obtained dialysate to ultra-high-speed centrifugation at 1,5000 rpm, and then separating by nanofiltration, the obtained light yellow nanoparticles are repeatedly washed with ultrapure water and acetone, and then placed in the air to dry overnight. The transmission electron microscope image of the material is shown in the attached figure. Figure 1 The X-ray diffraction pattern is shown in the attached Figure 2 As shown, the molecular formula of the particles obtained at this time is Na 8 K 18 [Sc 12 (H 2 O) 6 (OH) 3 (HPO 4 ) 2 (Se 2 Mo 18 O 62 ) 3 ]·xH 2 O is a heteropolyacid compound with a vacancy-type Dawson structure; the solid particles are placed in a quartz boat, calcined in a vacuum oven at 350°C for 1 hour, and the obtained black sample is immersed in an imidazole solution; the solid particles immersed in imidazole are poured into a ball mill, and the grinding is continued for 3 hours, and the solid particles are dialyzed again using a 10,000Da dialysis bag overnight, and the dialysate is subjected to ultra-high-speed centrifugation at 1,5000 rpm, and then separated by nanofiltration to obtain nanoparticles; the nanoparticles are dispersed in a Nafi having a mass concentration of 5% on solution, at which the mass concentration of the nanoparticles is 20%, and dispersed under 1kW ultra-high frequency ultrasound for 5 minutes to form a uniformly dispersed nanoparticle solution; the above nanoparticle solution is uniformly coated on the surface of hydrophilic carbon paper, wherein the hydrophilic carbon paper that can be selected can be one of the TGP-H-60 series of Toray Company of Japan, the SGL-30 series of the United States, and the HCP010N series of carbon paper of Sanshou Company of Shanghai, China, and dried at 150°C for 15 minutes to obtain a carbon paper catalyst material with an oxygen evolution catalytic active coating.
[0031] Embodiment 2:
[0032] The carbon paper catalyst material having an oxygen evolution catalytic active coating obtained by the preparation method described in Example 1 was subjected to electrochemical testing.
[0033] A three-electrode system was constructed using a CHI-660D electrochemical workstation produced by Shanghai Chenhua Company to evaluate the electrocatalytic oxygen evolution (OER) activity of the prepared carbon paper catalyst material with an oxygen evolution catalytic active coating. Specifically, the carbon paper catalyst was used as the working electrode (WE), the platinum sheet was used as the counter electrode (CE), and the Hg / HgO electrode was used as the reference electrode (RE). -1 Linear sweep voltammetry (LSV) test was performed in an alkaline environment of KOH. During the test, the voltage was set at 5mV s -1 The scan rate was 1.500 nm and the linear scan was performed in the range of +1.4 to +2.0 V relative to the reversible hydrogen electrode (RHE). The conversion of the electrode potential relative to the standard hydrogen electrode was based on the formula E RHE =0.098V+pH×0.059V for correction.
[0034] The carbon paper catalyst material with oxygen evolution catalytic active coating obtained above was subjected to linear sweep voltammetry scanning of an electrochemical workstation, and the results are shown in the attached figure. Figure 3 As shown in Figure 2, its oxygen evolution potential (OEP is about 1.49 V vs. RHE) is better than that of carbon paper and RuO 2 electrode.
[0035] Embodiment 3:
[0036] The carbon paper catalyst material having an oxygen evolution catalytic active coating obtained by the preparation method described in Example 1 was subjected to electrochemical testing.
[0037] The electrochemical workstation and electrode configuration were the same as in Example 2, and the cyclic voltammetry (CV) method was used. -1 The scan was performed in KOH electrolyte, with the non-Faraday region of the electrode (0.1-0.2 V vs. RHE) selected as the scanning range and the scanning speed was 10 to 60 mV s -1 CV scans were performed at different scan rates. Subsequently, the equivalent electrochemical active area (ECSA) value was calculated by plotting and fitting the CV curves of the same sample at different scan rates. The size of the ECSA value directly reflects the number of active sites on the electrode surface.
[0038] It is calculated that the ECSA of the carbon paper catalyst material with oxygen evolution catalytic active coating prepared in Example 1 is 156 cm 2 , much larger than carbon paper and RuO 2 12.5cm of electrode 2 and 96cm 2 . It has more surface active sites.
[0039] Embodiment 4:
[0040] The carbon paper catalyst material having an oxygen evolution catalytic active coating obtained by the preparation method described in Example 1 was subjected to electrochemical testing.
[0041] The electrochemical workstation and electrode configurations were as in Example 2, and the electrode samples were subjected to electrochemical impedance spectroscopy (EIS) testing to analyze the charge transfer characteristics of the electrode interface. The test was performed at a bias voltage of 250 mV relative to RHE, with a frequency range of 100 mHz to 100 kHz, and a fixed amplitude of 10 mV.
[0042] It is calculated that the Tafel slope of the carbon paper catalyst material with oxygen evolution catalytic active coating prepared in Example 1 is 115.27 mV dec -1 , with carbon paper and RuO 2 The Tafel slope of the electrode is 165.42 mV dec -1 and 105.16mV dec -1 Similarly, it shows that the catalyst active layer does not affect the charge transfer.
[0043] Embodiment 5:
[0044] The carbon paper catalyst material having an oxygen evolution catalytic active coating obtained by the preparation method described in Example 1 was subjected to electrochemical testing.
[0045] The electrochemical workstation and electrode configuration were the same as in Example 2. The accelerated durability test (ADT) and chronopotentiometry curve test were used. The ADT test was performed in the linear scanning range of 0.1-0.3 V vs. RHE at 0.1 V s -1 After 10000 cycles of CV scanning, the LSV test was performed again, focusing on the electrode at 10 mA cm -2 Change of overpotential with current density.
[0046] The chronopotentiometry curves were measured at room temperature at a constant 10 mA cm -2 The current density was measured, and the stability change of the overpotential was continuously monitored and recorded. The test duration was set to 240 h.
[0047] The results show that the carbon paper catalyst material with oxygen evolution catalytic active coating prepared in Example 1 has good electrochemical activity and stability. After a test period of 240 hours, although the overpotential fluctuates greatly due to the long-term alkali solution immersion and swelling, the average electrode overpotential changes by only 55 mV. Relatively speaking, the carbon paper also does not show significant changes. 2 The electrode showed a significant increase in overpotential at 117 h, and after 240 h of testing, its activity was completely lost and it no longer had OER catalytic activity.
[0048] The specific implementation methods described above are only used to specifically illustrate the spirit of the present invention, and the protection scope of the present invention is not limited thereto. For those skilled in the art, other implementation methods can certainly be easily made by changing, replacing or modifying the technical contents disclosed in this specification, and these other implementation methods should all be included in the protection scope of the present invention.
Claims
1. A base metal low oxygen evolution potential electrode for solid polymer water electrolysis, characterized in that: The preparation method of the electrode comprises the following steps: Step 1, after grinding SeCl4 and (NH4)2MoO4 in a molar ratio of 1:9 in a mortar, adding them into ultrapure water, stirring vigorously, and preparing a light yellow aqueous solution with a mixed mass concentration of 10%; Step 2, adjusting the pH value of the light yellow aqueous solution obtained in step 1 to 4 with phosphoric acid, adding excess ScCl3 until it is completely dissolved, at which point the molar ratio of Sc to Se should be greater than 2, to obtain solution A; Step 3, preparing a mixed solution of NaOH and KOH with a molar ratio of 4:9 and a mixed mass concentration of 25% to obtain a mixed alkaline solution B; Step 4, adding the mixed alkali solution B obtained in step 3 dropwise into solution A, and monitoring the change of pH value, when the pH value reaches 6, the solution gradually becomes turbid, at which time the dropping is stopped and the solution is stirred vigorously, a large amount of flocs are quickly formed in solution A, but are broken again with stirring; Step 5, after continuous stirring for 30 minutes, stop stirring, transfer to a 10,000Da dialysis bag for overnight dialysis, subject the obtained dialysate to ultra-high-speed centrifugation at 1,5000 rpm, and then separate by nanofiltration, and the obtained light yellow nanoparticles are repeatedly washed with ultrapure water and acetone, and then placed in the air to dry overnight; Step 6, placing the solid particles obtained in step 5 into a quartz boat, calcining in a vacuum oven at 350° C. for 1 hour, and immersing the obtained black sample in an imidazole solution; Step 7, pouring the solid particles soaked in imidazole obtained in step 6 into a ball mill, grinding for 3 hours, dialyzing again with a 10,000Da dialysis bag overnight, subjecting the obtained dialysate to ultra-high-speed centrifugation at 1,5000 rpm, and then separating by nanofiltration to obtain nanoparticles; Step 8, dispersing the nanoparticles obtained in step 7 in a Nafion solution with a mass concentration of 5%, at which point the mass concentration of the nanoparticles is 20%, and dispersing the solution under 1 kW ultrahigh frequency ultrasound for 5 minutes to form a uniformly dispersed nanoparticle solution; Step 9, uniformly coating the nanoparticle solution obtained in step 8 on the surface of the hydrophilic carbon paper, and drying at 150° C. for 15 minutes to obtain a carbon paper catalyst material having an oxygen evolution catalytic active coating.
2. A base metal low oxygen evolution potential electrode for solid polymer water electrolysis and a preparation method thereof as claimed in claim 1, characterized in that: The purity of NaOH and KOH described in step 3 should be higher than 95%. The mixture should be sealed immediately after preparation to prevent absorption of CO2 in the air and generation of bicarbonate, which may affect the purity of the product.
3. A base metal low oxygen evolution potential electrode for solid polymer water electrolysis and a preparation method thereof as claimed in claim 1, characterized in that: The molecular formula of the particles obtained in step 5 is Na8K 18 [Sc 12 (H2O)6(OH)3(HPO4)2(Se2Mo 18 O 62 )3]·xH2O is a heteropolyacid compound with a vacancy-type Dawson structure.
4. A base metal low oxygen evolution potential electrode for solid polymer water electrolysis and a preparation method thereof as claimed in claim 1, characterized in that: The hydrophilic carbon paper selected in step 9 can be TGP-H-60 series carbon paper of Toray Industries, Japan, SGL-30 series carbon paper of the United States, or HCP010N series carbon paper of Sanshou Company, Shanghai, China.
Citation Information
Patent Citations
Electrolytic water oxygen evolution catalyst FeCoNi LDH / CuO / Cu and preparation method thereof
CN113957455A
Nickel-iron-based catalyst as well as preparation and application thereof
CN114289021A
Electrode, method for producing same, water electrolysis device, and fuel cell
CN116234942A
Electrolyzed water oxygen evolution catalyst and preparation method thereof
CN117626332A
Colloidal-copper based water oxidation electrocatalyst
US20210237037A1